Evaluation of the potential for struvite and calcite formation at seven sewage treatment works within the Severn Trent region - Wall, F. (Cranfield University, 2000)
Scale formation on the pipes, pumps and dewatering equipment succeeding anaerobic digesters leads to reduced hydraulic capacity and increased downtime and pumping costs. The increasing use of biological nutrient removal (BNR), in particular biological phosphorus removal (BPR) leads to the production of phosphorus rich sludges. Anaerobic digestion solubilises ammonia, magnesium and orthophosphates (stored with micro-organisms) which are then available for scale formation. Scale formation in pipes means either replacement or repeated scouring, the expense and inconvenience involved with such measures demand research into the extent of the problem within the Severn Trent region. During this extensive study of seven full-scale sewage treatment works (STWs) throughout the Severn Trent region, the levels of scale forming elements within digested sludge liquors and centrate were monitored. Sampling took place on a weekly basis over a period of six weeks. A computer model was used to evaluate the struvite or calcite formation potential of the liquors and centrate. The model is affected by concentrations of the key elements phosphorus, calcium, magnesium and ammonia, in addition to pH, total dissolved solids and alkalinity. A strong correlation has been found between the models predictions and reality. Four out of the seven works were predicted to have a scale problem by the model, and by the end of the project, this was indeed the case. The type of scale forming was also correctly predicted, though the degree of scale formation was not always as predicted. Bench-scale experiments with real sludge liquors are planned to validate the precipitation potentials indicated by the model. This will allow Severn Trent to take a more proactive approach to the growing scale problem.